2023
DOI: 10.1111/spol.12902
|View full text |Cite
|
Sign up to set email alerts
|

Beyond path dependency: Analysing Indonesia's social policy responses to two crises

Abstract: This article sets out a coherent framework for debates and discussions on social policy changes during crisis periods. Using Indonesia as a case, this article compares its social policy responses to the 1997–1998 economic crisis and the current COVID‐19 pandemic crisis. Both two crises and their responses, once analysed, lead to an argument that path dependence does not always dominate policy processes, as most literature claims, but rather it operates alongside other path‐creation‐related processes, such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…The authorities had to intervene due to interruptions of social services and made innovations which were policy responses to deal with the situation that emerged because of the pandemic. The study investigated policy responses and changes in social services deploying the theories of institutionalism (Cruz‐Martínez et al., 2023; Hall, 1993; Hogan et al., 2022; Yuda, 2023; Yuda et al., 2022). It revealed that the nature and delivery system of social service programs had been changed due to the quick spread of COVID‐19 which was a short‐term policy response also found in many other studies (Cruz‐Martínez et al., 2023; Dorlach, 2023; Hogan et al., 2022; Yuda et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authorities had to intervene due to interruptions of social services and made innovations which were policy responses to deal with the situation that emerged because of the pandemic. The study investigated policy responses and changes in social services deploying the theories of institutionalism (Cruz‐Martínez et al., 2023; Hall, 1993; Hogan et al., 2022; Yuda, 2023; Yuda et al., 2022). It revealed that the nature and delivery system of social service programs had been changed due to the quick spread of COVID‐19 which was a short‐term policy response also found in many other studies (Cruz‐Martínez et al., 2023; Dorlach, 2023; Hogan et al., 2022; Yuda et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Yuda (2023) also noticed similar changes in Indonesia and claimed that the pandemic didn't create a conducive environment to have major revisions in current social policies. He pointed out that introducing unemployment insurance during COVID-19 was a path-breaking, which later became institutionalized (Yuda, 2023). In a similar vein, Yuda et al (2022) pointed out that COVID-19-affected countries like Indonesia, Malaysia, the Philippines, and Thailand launched some social protection programs temporarily without any basic modification.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Focusing specifically on the Indonesian case, this paper aims to contribute to the growing body of research on welfare stereotypes and stigma (Dukelow et al, 2022). To our knowledge, this topic has not yet been explored in relation to conditional cash transfer (CCT) programs, particularly in Southeast Asia as emerging welfare capitalism (Sumarto, 2020a; Yuda, 2023; Yuda et al, 2022; Yuda & Kühner, 2022). Accordingly, our paper outlines its objectives, which include examining the effects of CCT on impoverished families, exploring their attitudes towards these programs in response to stereotyping, and considering the implications of such stereotypes for the claim motivation of claimants.…”
Section: Introductionmentioning
confidence: 99%